Real-Life International Normalized Ratio Profile in Patients with Non-Valvular Atrial Fibrillation Prescribed Vitamin K Antagonist - S. I. Farag; O. S. Arafa; A.A. E. Hassan; H. M. Mashhour; A. M. Bendary (Рациональная фармакотерапия в кардиологии)
Coagulation status with vitamin K antagonists (VKAs) needs to be monitored carefully to ensure maximal efficacy with minimal complication rates.Aim. To study the international normalized ratio (INR) values in patients on VKAs in selected area, find out which patient characteristics that is associated with good INR control and calculation of the time in the therapeutic range (TTR) according to the number of INR/Patient.Material and methods. A total of 200 patients with non-valvular atrial fibrillation prescribed vitamin K antagonist as anticoagulant were evaluated. They were divided into two groups: group I with TTR≥65% (n=93) and group II with TTR<65% (n=107). Stroke and hemorrhagic risks were calculated by means of the CHA2DS2-VASc score and HAS-BLED score, respectively. Presence of comorbid diseases was assessed by the Charlson index. TTR was calculated using Rosendaal method.Results. Patients in group I (TTR≥65%) were younger (p<0.001), more often men (p<0.074) with a high level of education (p<0.001), had lower stroke and hemorrhagic risks (mean CHA2DS2-VASc score was 1.0 and HAS-BLED score – 0.0), and also had fewer comorbidities (mean Charlson index was 0.0; p<0.001) compared to patients in group II (TTR<65%). The rate of inadequate control with VKAs (TTR<65) was 52%. Multivariate logistic regression analysis was done to see the significant independent predictors for a good INR control i.e. TTR≥65%. It was found that high level of education compared to lower levels is the only significant independent predictor for obtaining good INR control (odds ratio=133, 95% confidence interval 34.24-514.44, p<0.001).Conclusion. It was found that high level of education compared to lower levels is the only significant independent predictor for obtaining good INR control.